Recent advancements in semiconductor materials for photoelectrochemical water splitting for hydrogen production using visible light. (June 2018) - Saraswat, Sushil Kumar; Rodene, Dylan D.; Gupta, Ram B.
Abstract: Water splitting technology directly stores solar energy into the chemical bonds of diatomic hydrogen to be used as a clean fuel without producing any unwanted side reactions, byproducts or environmentally polluting compounds. Semiconductor materials are needed for a photoelectrochemical (PEC) device to catalytically convert photons from sunlight into chemical energy. Materials implemented in a device for sustainable hydrogen production are required to be inexpensive, highly photo-active, chemically stable, environmentally sustainable, and have a high solar-to-hydrogen conversion efficiency. Although many semiconductor composites and nanostructures have been examined, thus far, no material satisfies all criteria of an implementable photocatalyst and many materials do not show necessary energy conversion efficiency. Materials that depicted a high efficiency often rely on the ultraviolet portion of the solar spectrum, which does not contain enough energy for the industrial utilization of PEC water splitting technologies. Focusing on the use of the visible spectrum is promising for hydrogen production. Herein, recent advancements in the activity of visible light semiconductors are presented, including both platinum and non-platinum group materials. This review touches on the latest developments in various synthesis schemes capable of achieving suitable water splitting compositions and architectures while highlighting the challenges being faced when designing visible light-active water splitting photocatalysts. Interesting advancements in the use of nanostructures for designing the next generation of catalysts will be discussed. Also, for the proper comparison of catalytic efficiencies, it is important to establish terminology that can compare data across a magnitude of experimental conditions. A notable challenge associated with the catalysis is its stability or photocorrosion, which lacks established protocols. Promising future directions for designing next generation materials are discussed. Highlights: PEC water splitting, a promising technology for renewable hydrogen production. Highlights recent innovations of photocatalysts including schemes and modifications. Emphasis on visible light photo-absorbers to improve solar-to-hydrogen efficiencies. Discusses both platinum and non-platinum group metals photocatalysts. Focuses on water splitting fundamentals, efficiencies, stabilities & advancements.